Crystal structure of the motor domain of a class-I myosin - Kollmar, Martin (Oxford University Press, 2002)
The crystal structure of the motor domain of Dictyostelium discoideum myosin-IE, a monomeric unconventional myosin, was determined. The crystallographic asymmetric unit contains four independently resolved molecules, highlighting regions that undergo large conformational changes. Differences are particularly pronounced in the actin binding region and the converter domain. The changes in position of the converter domain reflect movements both parallel to and perpendicular to the actin axis. The orientation of the converter domain is ∼30° further up than in other myosin structures, indicating that MyoE can produce a larger power stroke by rotating its lever arm through a larger angle. The role of extended loops near the actin-binding site is discussed in the context of cellular localization. The core regions of the motor domain are similar, and the structure reveals how that core is stabilized in the absence of an N-terminal SH3-like domain.